Anaesthesia in Congenital Facial Anomalies in a Rural Set up of a Developing Country - Debasish Saha; Arunima Chaudhuri; Sumanta Ghosh Maulik; Sarbari Swaika; Debasish Ghosh; S. A. Faizal (Journal of Krishna Institute of Medical Sciences University)
Background: India has an estimated backlog of 1000000 cleft patients. A total of 35000 new cleft patients are born each year. With the capacity to operate on approximately 50000 patients each year only 15000 patients from the national backlog can be operated upon each year if capability is not augmented. Objectives: To reach the population at large we meticulously planned an out-reach programme and operated on patients even in rural set ups with lack of modern facilities. We operated on patients at sub divisional centres, where apparatus for providing sevoflurane was not available. Institutional Ethical clearance was taken before conduction of the study. Patients who required prolonged surgery were taken to the tertiary centre. Working ventilators were also not available at peripheral centres. Materials and Methods: This interventional study was carried in a time span of four years on nineteen hundred and nine patients, after taking approval from the Institutional Ethical Committee. Patients were screened and some were operated at rural centers and others at a tertiary care centre. Patients who could not afford to come to the tertiary care centre were operated at different rural centers. Informed consent was taken. Results: There were 1909 patients with Congenital Facial Anomalies (CFA) over four years period out of which 918 patients were of either unilateral or bilateral cleft lip. They were successfully operated at rural health centers with limited facilities. This could reduce the total load of surgeries for CFA at tertiary care hospital ensuring safe surgeries for all with CFA for all age groups and both genders.No mortality was recorded and post operative complications consisted of nausea and vomiting, three had delayed recovery and one had laryngospasm. Conclusion: Outreach programmes can increase the efficacy of Smile Train Project and effective screening of patients before surgery can result in fruitful outcomes even in a rural set up with lack of modern anaesthetic facilities.